A first-year maize/cassava relay intercropping system improves soil nutrients and changes the soil microbial community in the symbiotic period - He, Cuicui; Zhou, Bin; Wang, Hua; Wei, Yunxia; Huang, Jie (Frontiers in Microbiology, 2023)
The maize/cassava relay intercropping system can be a specific and efficient cropping pattern in a tropical/subtropical field. Relay intercropping systems contribute to the optimization of land use, fostering sustainable and efficient agriculture. This study entails a first-year comparative intercropping experiment using maize (Zea mays L.) and cassava (Manihot esculenta Crantz). We determined the soil nutrient contents and physicochemical properties as well as the microbial communities by high-throughput sequencing. We found that the relay intercropping system changed the bacterial community structure, especially the rhizosphere microorganisms. The bacterial community was characterized by a higher abundance of the phyla Chloroflexi, Proteobacteria and Actinobacteria and of the genus AD3, which are related to nutrient cycling and decreased bioavailability of Cd. At the same time, the relay intercropping system reduces the relative abundance of pathogenic bacteria and biomarkers of organic pollution. The relay intercropping systems significantly boosted soil pH and available K levels in addition to the monocropping yield. The results of this study suggest that maize/cassava relay intercropping, starting from the first year, not only provides a stable supply of food and income due to the diversified cropping systems but is also beneficial for the improvement of soil quality and the soil microbial community.